x+17=(-7,-1,1,7)
y-3=(-1,-7,7,1)
=>
x=(-24,-18,-16,-10)
y=(2,-4,10,4)
(xy)+(-24,2);(-18,-4);(-16,10);(-10,4)
b) x+1=(-3,-1,1,3)=>(xy-1)=(-1,-3,3,1)=>xy=(0,-2,4,2)
x=(-4,-2,0,-2)
y=(0,1,-1)=> loiaj x=0
DS:
(x,y)=(-4,0);(-2,1);,(-2,-1)
c) tý nũa ăn com đã
c)xy+12=x+y
x(y-1)+11=(y-1)
(y-1)(1-x)=11
1-x=(-11,-1,1,11)=> x=(12,2,0,-10)
y-1=(-1,-11,11,1)=> y=(0,-10,12,2)
(xy)=(12,0);(2,-10),;(0,12):,(-10,2)
d)
2x-1=(-11,-1,1,11)=> x=(-5,0,1,6)
y+4=(-1,-11,11,1)=> y=(-5,-15,7,-3)
(x,y)=(-5,-5),;(0,-1); (1,7); (6,-3)